Postural control of sway dynamics on an unstable surface reduces similarity in activation patterns of synergistic lower leg muscles - Mademli, Lida; Nikolaidou, Maria-Elissavet; Bohm, Sebastian; Arampatzis, Adamantios (Frontiers in Sports and Active Living, 2025)
IntroductionDiversity of activation patterns within synergistic muscles can be important for stability control in challenging conditions. This study investigates the similarity of activation patterns within the triceps surae and quadriceps femoris muscles and the effects of unstable surface during a visually guided postural task.MethodsEighteen healthy adults performed a visually guided anteroposterior tracking task on both stable and unstable surfaces. Electromyographic activity of triceps surae (gastrocnemius medialis, gastrocnemius lateralis, soleus) and quadriceps femoris (vastus medialis, vastus lateralis, rectus femoris) was recorded at 1,000 Hz. Cosine similarity (CS) between muscle pairs within each muscle group was calculated to assess the similarity of activation patterns of synergistic muscles for stable and unstable conditions. To compare the CS of the muscle pairs, a linear mixed model was used. For all tests the level of significance was set to α = 0.05.ResultsAcross all surface conditions, CS values within the triceps surae muscles were lower than those of the quadriceps (p < 0.001), indicating a greater diversity in activation patterns of the distal muscles. The unstable surface reduced CS values for both muscle groups (p = 0.021). No significant interaction was observed between muscle pair and surface condition (p = 0.833).DiscussionThe reduced similarity of activation patterns within the synergistic triceps surae and quadriceps femoris muscles on the soft surface indicates an increased flexibility of neuromotor control for the unstable condition. The lower similarity within the synergistic triceps surae muscles suggests a higher diversity of activation patterns compared to the quadriceps femoris muscles, which may increase the flexibility of neuromotor control to meet specific joint stabilization challenges during the studied tracking task.